Impact of fatigue and insufficient sleep on physician and patient outcomes: a systematic review. Issue 9 (21st September 2018) - Gates, Michelle; Wingert, Aireen; Featherstone, Robin; Samuels, Charles; Simon, Christopher; Dyson, Michele P
Abstract : Objectives: For physicians in independent practice, we synthesised evidence on the (1) impacts of insufficient sleep and fatigue on health and performance, and patient safety and (2) effectiveness of interventions targeting insufficient sleep and fatigue. Design: We systematically reviewed online literature. After piloting, one reviewer selected studies by title and abstract; full texts were then reviewed in duplicate. One reviewer extracted data; another verified a random 10% sample. Two reviewers assessed risk of bias. We pooled findings via meta-analysis when appropriate or narratively. Data sources: We searched Medline, Embase, PsycINFO, CINAHL and PubMed for published studies in April 2016; Medline was updated in November 2017. We searched Embase for conference proceedings, and hand-searched meeting abstracts, association and foundation websites. Eligibility criteria for selecting studies: English or French language primary research studies published from 2000 to 2017 examining the effect of fatigue-related or sleep-related exposures or interventions on any outcome among physicians in independent practice and their patients. Results: Of 16 154 records identified, we included 47 quantitative studies of variable quality. 28 studies showed associations between fatigue or insufficient sleep and physician health and well-being outcomes. 21 studies showed no association with surgical performance, and mixed findings for psychomotor performance, work performance and medical errors. We pooled data from six cohort studies for patient outcomes. For sleep deprived versus non-sleep deprived surgeons, we found no difference in patient mortality (n=60 436, relative risk (RR) 0.98, 95% CI 0.84 to 1.15, I 2 =0% (p=0.87)) nor postoperative complications (n=60 201, RR 0.99, 95% CI 0.95 to 1.03, I 2 =0% (p=0.45)). The findings for intraoperative complications and length of stay were considerably heterogeneous. Conclusions: Fatigue and insufficient sleep may be associated with negative physician health outcomes. Current evidence is inadequate to inform practice recommendations.